Analysis of The Effect of Company Size, Profitability and Leverage on Systematic Risk (An Empirical Study of Companies Listed on the Indonesia Stock Exchange Indexed LQ-45 for the Period 2019–2023) - Kurniatin, Esti; Ismail, Tubagus; Yuniarti, Rita (Journal of Accounting and Finance Management, 2025)
The aims of this quantitative research are to identify and analyze company size, profitability and leverage which are part of internal factors or company fundamentals and their influence on systematic risk in LQ - 45 indexed companies for the period 2019 - 2023. The high beta value of stocks as a tool for assessing of systematic risk is the reason for the need for further observation on the factors that may influence it. Financial statements are used as objects in the research, purposive sampling method is used in withdrawing samples. Secondary data and combined data between time series and cross sectional data were used in the study, and panel regression analysis was conducted using Eviews 13 software to answer the proposed hypotheses. In selecting the best model to be used in panel data regression analysis, Chow's test and Hausman's test were required, resulting in the Fixed Effects Model being selected as the best model. Partial hypothesis testing using the t-test shows that the company size variable using a natural logarithm proxy of total assets and the profitability variable using a return on assets proxy have no significant effect on systematic risk. However, the t test results of the leverage variable with the debt to equity ratio proxy show different results, namely the leverage variable is the only variable that has a positive & significant effect on systematic risk.